Anti Inflammatory And Anti Bacterial Activity Of Sumbawa Oil - Sugara, Taufan Hari; Nurbaety, Baiq (Pharmaciana, 2018)
Sumbawa oil is a traditional ingredient that known as local wisdom of the island society of Sumbawa. It is believed to treat wounds, sprains, rheumatism, thrush and toothache. This study aims to determine the the effectiveness of anti-inflammatory and antibacterial activity of sumbawa oil products based on the types of raw materials and its phytochemical compounds. There are 3 stages in this research, consists of collecting various trademark of sumbawa oil product, determining type of raw material and analysis of phytochemical compound, followed by pharmacological activity test (Anti-inflammatory and antibacterial). Anti-inflammatory test was performed by observing the decrease of percentage inflammation of 21 white rats in 7 groups of egg white injection treatment. Antibacterial test using TSA method by observing the inhibition zone against S. aureus and E. coli bacteria. The results showed that Sumbawa oil products are known to contain secondary metabolite compounds of saponins, Triterpenoids, steroids and Flavonoids. All samples of Sumbawa oil products showed anti-inflammatory activity based on a decrease in the percentage of inflammation in the white rats leg for 6 hours of observation. Sumbawa oil also shows antibacterial activity in the strong category and has a wide spectrum because it can inhibit the growth of gram positive and negative bacteria each of 11,83-14,67 mm and 10,67-12,33 mm.Â  This study concluded that Sumbawa oil was shown to have antiinflamatory and antibacterial activity even though its value was still lower than standard drug.